Pengembangan Media Pembelajaran dengan Bantuan Aplikasi Mtestm Kemampuan Mendengar A1 - Adinda Putri Nazli; Risnovita Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to create learning media with the help of MtestM application about German language students' knowledge of listening skill A1 topic